The relationship between empathy and school adjustment of left-behind children: The mediating role of coping styles - Qin, Guihua; Xie, Ruibo; Wang, Die; Wu, Wei; Wan, Simin; Li, Weijian (Frontiers in Psychology, 2022)
To investigate the effects of left-behind children’s empathy and coping styles on school adjustment, 605 left-behind children in the third grade from three rural elementary schools in Suzhou, Anhui Province were selected to complete the Chinese version of the Interpersonal Reaction Index Scale, the Coping Style Scale, and the School Adjustment Behavior Scale for Primary and Secondary School Students. The results showed that (1) emotional empathy positively predicted children’s social competence, and negatively predicted children’s antisocial behavior; cognitive empathy positively predicted children’s social competence; (2) the role of positive coping styles mediated the relationship between cognitive empathy and social competence, and that between cognitive empathy and antisocial behavior; negative coping styles mediated the relationship between cognitive empathy and antisocial behavior; both positive and negative coping styles mediated the relationship between emotional empathy and social competence, and that between emotional empathy and antisocial behavior. The findings of the study are valuable for understanding the relationship between empathy and school adjustment, which also helps to enhance the school adjustment of left-behind children.